Dependence of the polytropic index of plasma on magnetic field - June Young Kim; Geunwoo Go; Y S Hwang; Kyoung-Jae Chung (New Journal of Physics, 2021)
Determination of the polytropic index of plasma in a magnetic field provides description of plasma physics ranging from laboratory plasma in the Earth to black hole in the Universe. Accordingly, a lot of efforts have been devoted to revealing the dependence of polytropic index of plasma on magnetic field. A recent experiment performed in a magnetic nozzle reported the dependency of the polytropic index on the magnetic field strength in that the polytropic index changes from 5/3 to unity with decreasing the magnetic field strength. In this letter, we show that the polytropic index of plasma does not depend on magnetic field if the radial electric field is sustained. The polytropic index is measured to be close to 2, higher than the previously reported value, regardless of the change in the strength and configuration of magnetic field.